Analysis of Handover Schemes in IEEE 802.16 (WiMAX) - Saini, Mohit (My University, 2008)
Enterprises, Internet Service Providers, and Mobile Network Operators are all looking for cost-effective ways to move data ,voice and video amongst multiple, separate locations at broadband speeds. Copper and fiber optics solutions often fall short due to up-front costs, recurring leases from telecommunications companies, and a lack of flexibility to scale with the operating organization. Broadband Wireless has emerged as a means to fill these gaps and to provide a lower total cost of ownership than wired solutions, while maintaining or exceeding the reliability and performance of those technologies. The IEEE 802.16 family of standards and its associated industry consortium, WiMAX, promises to deliver high data rates over large areas to a large number of users in the near future. This exciting addition to current broadband options such as DSL, Cable, and WiFi promises to rapidly provide broadband access to locations in the world’s rural and developing areas where broadband is currently unavailable. It is also necessary to provide Quality of Service (QOS) guaranteed with different characteristics for Broadband Wireless Access (BWA) networks. Major issue concerning implementation of WiMAX is to provide effective handover. Considering QOS parameters it becomes necessary to provide handover process to be as fast as possible. Various fast handover techniques have been suggested in literature to meet QOS requirements. This thesis explains handover process in WiMAX along with different handover techniques. Various Fast handover techniques explained include Cost effective Target Base Station Selection, Fast Ranging and Pre-registration. Effect of these Handover Techniques on the WiMAX parameters like Scanning Time and Handover Latency have been studied taking assumptions into consideration. By extensive simulation it has been shown that these fast handover schemes when combined reduce the scan time and handover latency during handover process and increase the overall performance of WiMAX handover process. KeyWords: Handover, Cost Effective Target BS Selection (CTBS), IEEE 802.16, WiMAX
M.E. (CSED)
Keywords: Handover; Wi-Max